Investigating the Activity of Carbon Fiber Electrode for Electricity Generation from Waste Potatoes in a Single-Chambered Microbial Fuel Cell. (27th January 2023) - Din, Muhammad Imran; Ahmed, Mahmood; Ahmad, Muhammad; Iqbal, Mahroosh; Ahmad, Zahoor; Hussain, Zaib; Khalid, Rida; Samad, Abdul
Abstract : Microbial fuel cells (MFCs), a technology that converts chemical energy into electrical energy, have been regarded as the most suitable method for sustainable energy production. However, most MFCs generate a low power output, limiting their large-scale industrial applications. Here, we introduce a high-performancesingle-chambered microbial fuel cell (SCMFC) based on carbon fiber anode and zinc oxide nanoparticle (ZnO NP)-fabricated copper cathode. Furthermore, best optimized conditions of temperature, pH, substrate, external resistance, and cathode fabrication were also considered to evaluate the performance of this SCMFC in treating potato wastewater along with bioenergy production. Results indicated that chemical oxygen demand (COD) could be effectively removed (80%) and maximum voltage, current density, and power density were 1.58 V, 0.235 mA/cm 2, and 0.3714 mW/cm 2, respectively. Hence, the SCMFC used in this study has a higher potential to treat potato wastewater along with high power production.